Jämförelsekonstruktioner i Svensk konstruktionsordbok – struktur, variation och funktion - Clausén, Ulla (Nordiske Studier i Leksikografi, 2003)
This paper deals with different types of comparative constructions, which I have found in the forthcoming dictionary Svensk konstruktionsordbok. A well known type is similes, such as something is as heavy as lead. Other types which I am going to introduce are concrete comparisons, comparative collocations, comparative proverbial phrases and comparative pragmatic phrases (Figure 1). I am going to analyse the structure and function of the different types of comparative constructions. The result is given in a model of analysis of comparative constructions in Svensk konstruktionsordbok (Figure 2).